2015
DOI: 10.1002/tox.22111
|View full text |Cite
|
Sign up to set email alerts
|

The role of multifunctional drug therapy as an antidote to combat experimental subacute neurotoxicity induced by organophosphate pesticides

Abstract: Organophosphate pesticides are used in agriculture where they are associated with numerous cases of intentional and accidental misuse. These toxicants are potent inhibitors of cholinesterases leading to a massive build-up of acetylcholine which induces an array of deleterious effects, including convulsions, oxidative damage and neurobehavioral deficits. Antidotal therapies with atropine and oxime yield a remarkable survival rate, but fail to prevent neuronal damage and behavioral problems. It has been indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It has been reported that chronic administration of chlorpyrifos significantly impaired learning, memory, and motor coordination [ 63 ]. Exposure to pesticides such as parathion, hexachlorocyclohexane, and aldrin resulted in an increased risk of dementia and the subsequent onset of Alzheimer’s disease [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that chronic administration of chlorpyrifos significantly impaired learning, memory, and motor coordination [ 63 ]. Exposure to pesticides such as parathion, hexachlorocyclohexane, and aldrin resulted in an increased risk of dementia and the subsequent onset of Alzheimer’s disease [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of AChE leads to the accumulation of acetylcholine in the synapses, which leads to continuous overstimulation of the nervous system, thus probably leading to the death of the organism [ 42 ]. Different doses of CPF have been reported to inhibit acetylcholinesterase, causing acetylcholine accumulation in synaptosomes, thereby inducing learning and memory dysfunction [ 43 , 44 ]. Evidently, CPF can inhibit acetylcholinesterase activity through promoting serine site phosphorylation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Testis damage was induced in the exposure groups by intraperitoneal injection of CPF in DMSO at doses of 1.0 and 3.0 mg/kg body weight (b. wt) (Slotkin, Levin, & Seidler, ). Injections were performed 5 days a week (single daily injection) for 2, 4 or 6 consecutive weeks (Singh et al, ; Singh & Panwar, ; Wang et al, ). Rats in the vehicle‐treated control group (sham groups) were administered to the equal volume of vehicle (DMSO in 0.9% saline).…”
Section: Methodsmentioning
confidence: 99%